Sarekat Islam Penggagas Nasionalisme di Indonesia - soraya rasyid; Annisa Tamara (Universitas Islam Negeri Alauddin Makassar, 2020)
This paper aims to describe the existence of Sarekat Islam and its contribution in developing the Indonesian nationalism awareness. This paper is a historical writing by relying on literary studies. The results showed that the struggle of Sarekat Islam in the national movement has been able to foster Indonesian awareness of human values and their dignity as a nation. This consciousness developed into a national awareness with the growth of national unity ties between the people of Indonesia. The struggle of Sarekat Islam also made the Dutch colonial government realize about the desire of Indonesian people to achieve independence. Internal conflicts have slowly divided Sarekat Islam, thus weakening its struggle in the national movement. However, Sarekat Islam played an important role in realizing the independence of the Republic of Indonesia. The struggle and the track record of Sarekat Islam have placed this organization as a pioneer of nationalism in Indonesia.Tulisan ini bertujuan mendeskripsikan keberadaan Sarekat Islam dan kontribusinya dalam membangun kesadaran nasionalisme bangsa Indonesia. Tulisan ini merupakan tulisan sejarah dengan mengandalkan studi pustaka. Hasil tulisan menunjukan bahwa perjuangan Sarekat Islam dalam pergerakan nasional telah mampu menumbuhkan kesadaran rakyat Indonesia terhadap nilai manusia dan harga dirinya sebagai suatu bangsa. Kesadaran ini berkembang menjadi kesadaran nasional dengan tumbuhnya ikatan persatuan nasional antara rakyat Indonesia. Perjuangan Sarekat Islam juga menyadarkan pihak pemerintah kolonial Belanda terhadap keinginan rakyat Indonesia mencapai kemerdekaannya. Konflik internal secara pelan telah memecah Sarekat Islam sehingga melemahkan perjuangannya dalam pergerakan nasional. Meski demikian, Sarekat Islam tetap mempunyai peranan penting dalam mewujudkan kemerdekaan Republik Indonesia. Rekam jejak dan perjuangan Sarekat Islam telah menempatkannya sebagai organisasi pengagas Nasionalisme di Indonesia.